DEVELOPMENT OF THE SOUTHERN EASTERN CORDILLERA, NW ARGENTINA, CONSTRAINED BY APATITE FISSION TRACK THERMOCHRONOLOGY: FROM EARLY CRETACEOUS EXTENSION TO MIDDLE MIOCENE SHORTENING - Deeken A.; Sobel E.R.; Strecker M.R.; Coutand I.; Haschke M.; Riller U. (My University, 2006)
For the Puna Plateau and Eastern Cordillera of NW Argentina, the temporal and spatial pattern of deformation and surface uplift remain poorly constrained. Analysis of completely and partially reset apatite fission track samples collected from vertical profiles along an ESE trending transect extending from the plateau interior across the southern Eastern Cordillera at ~25°S reveals important constraints on the deformation and exhumation history of this part of the Andes. The data constrain the Neogene Andean development of the Eastern Cordillera as well as riftrelated exhumation for some of the sampled locations in the Late Jurassic/Early Cretaceous. An intervening Eocene-Oligocene exhumation episode in the southern Eastern Cordillera was probably related to crustal shortening. Subsequent reburial of the area by Andean foreland basin strata commenced between 30 and 25 Myr. Magnitude and duration of sedimentation, revealed by thermal modeling, differ between the sample locations, pointing to an eastward propagating basin system. In the southern Eastern Cordillera, Andean deformation commenced at 22.5-21 Myr, predating both the inferred formation of significant topography by 5-7.5 Myr and preservation of sediments in the adjacent Cenozoic basins by 6.5-8 Myr. Comparing the calculated structural depth of partially reset samples suggests that newly formed west dipping reverse faults along the former Salta Rift margin accommodated most of the Neogene tectonic movement. Late Cenozoic deformation at the southern Eastern Cordillera began earlier in the west and subsequently propagated eastward. The lateral growth of the orogen is coupled with a foreland basin system developing in front of the range and then becomes subsequently compartmentalized by later emergent topography. Copyright 2006 by the American Geophysical Union.
Keywords: Neogene; Cretaceous; Jurassic; Oligocene; Eocene; Cenozoic::Neogene; Кайнозой::Неоген; Mesozoic::Cretaceous; Мезозой::Меловая; Mesozoic::Jurassic; Мезозой::Юрская; Cenozoic::Paleogene::Oligocene; Кайнозой::Палеоген::Олигоцен; Cenozoic::Paleogene::Eocene; Кайнозой::Палеоген::Эоцен